PENGARUH KOMUNIKASI PERSUASIF TIKTOK LIVE TERHADAP KEPUTUSAN PEMBELIAN PADA AKUN TOKO SAMONO INDONESIA - Indra Saputra (Ensiklopedia Research and Community Service Review, 2026)
Abstract: This study aims to analyze the influence of persuasive communication in TikTok Live on purchasing decisions, specifically on the Samono Indonesia account. The approach used was quantitative with a descriptive design, where data was collected through a questionnaire distributed to 99 active buyers of Samono Indonesia products who follow its TikTok account. The research variables included psychodynamic, sociocultural, and constructive persuasive communication, and purchasing decisions. Data analysis was performed using multiple linear regression using SPSS 27.0. The results showed that psychodynamic persuasive communication had a positive and significant effect on purchasing decisions with a regression coefficient of 0.197 (p = 0.028). Sociocultural persuasive communication had the strongest effect with a coefficient of 0.477 (p = 0.000), while constructive persuasive communication also had a significant effect with a coefficient of 0.337 (p = 0.023). These three variables together explained 67.7% of the variation in purchasing decisions, with sociocultural persuasive communication being the most dominant factor. These findings indicate that in the context of TikTok Live, communication emphasizing social values, group norms, and community interaction is most effective in influencing consumer purchasing decisions. This research provides both theoretical and practical contributions, particularly in optimizing persuasive communication strategies for live shopping on digital platforms. For Samono Indonesia, the results suggest the importance of integrating sociocultural, constructive, and psychodynamic approaches into live content to increase audience engagement and drive sales.  Keywords: persuasive communication, psychodynamics, sociocultural, purchasing decisions, digital marketing.